Teachers’ Stories of Experience Guide Collaboration in Teacher Education - McPhie, Judith (Canadian Journal of Education/Revue canadienne de l'éducation, 1995)
The development and implementation of a program for the education of new teachers begins with teachers based in schools and teachers based in a university enquiring together into the knowledge that guides their work in education. This collaborative work requires a shift in the traditional roles and responsibilities of school- and university-based teachers. According to teachers’ recountings, five educational domains inform their professional decisions; these domains constitute the scaffolding on which the program is built. Collaboration can be characterized as ongoing and reflective processes that support participants in increased self-knowledge, and in increased knowledge of others’ perspec- tives and understandings. This provides the basis for the negotiation of new meaning. The weave of theory and practice challenges and deepens all participants’ knowledge, and increases the possibility of agreeing about what counts, in the beginning, for student teachers. L’élaboration et la mise en oeuvre d’un programme de formation des maîtres commencent lorsque les enseignants dans les écoles et les professeurs à l’université se penchent ensem- ble sur les connaissances qui orientent leur travail en éducation. Cette collaboration exige une transformation des rôles et des responsabilités traditionnellement dévolus aux ensei- gnants dans les écoles et aux professeurs dans les universités. Lorsque des enseignants racontent leurs expériences en matière de prise de décisions professionnelles, cinq facettes émergent; celles-ci constituent en quelque sorte l’échafaudage sur lequel repose le pro- gramme. La collaboration revêt la forme de processus de réflexion constants grâce aux- quels les participants parviennent à une meilleure connaissance d’eux-mêmes et des points de vue des autres. C’est sur cette base que se négocient les orientations nouvelles. Les relations intrinsèques entre la théorie et la pratique stimulent les participants, leur permettent d’approfondir leurs connaissances et améliorent les possibilités d’en venir à une entente sur ce qui, au début, compte pour les étudiants-maîtres.